Kawasaki Disease Complicated by Late-Onset Fatal Cerebral Infarction: A Case Report and Literature Review - Wang, Lin; Duan, Hongyu; Zhou, Kaiyu; Hua, Yimin; Liu, Xiaoliang; Wang, Chuan (Frontiers in Pediatrics, 2021)
Background: Cerebral infarction is a rare neurological complication of Kawasaki disease (KD), and occurs in the acute or subacute stage. There have been no reported cases of late-onset fatal cerebral infarction presenting over one year after the onset of KD. Case presentation: A five-month-old male patient with KD received timely intravenous immunoglobulin therapy; however, extensive coronary artery aneurysms (CAA) and coronary artery thrombosis (CAT) developed one month later. Anticoagulation and thrombolytic agents were suggested, but the child’s parents refused. Fifteen months after KD onset, an attack of syncope left him with left hemiplegia; brain computerised tomography (CT) scans revealed cerebral infarction of the right basal ganglion without haemorrhage. Magnetic resonance angiography (MRA) revealed severe stenosis of the right middle cerebral artery, and a series of tests were performed to exclude other causes of cerebral infarction. Considering the cerebral infarction and CAT, combination therapy with urokinase and low-molecular-weight heparin (LMWH) was initiated within 24 hours of syncope onset, together with oral aspirin and clopidogrel. Five days later, his clinical symptoms partially regressed and he was discharged. Unfortunately, five days after discharge, his clinical condition suddenly deteriorated. Repeat brain CT showed haemorrhagic stroke involving the entire left cerebral area, in addition to the previous cerebral infarction in the right basal ganglion, with obvious secondary cerebral swelling and oedema, which might have been caused by previous thrombolysis. Severe cerebral hernias developed quickly. Regrettably, the patient’s parents abandoned treatment because of economic factors and unfavourable prognosis, and he died soon after. Conclusions: Cerebral infarction and cerebral artery stenosis can develop late, even one year after the onset of KD. Paediatricians should be aware of the possibility of cerebrovascular involvement in addition to cardiac complications during long-term follow-up of KD patients. Prompt anticoagulation therapy and regular neuroimaging evaluation are essential for the management of patients with KD with giant CAA and/or CAT.